Effectiveness and safety of sofosbuvir plus ribavirin for the treatment of HCV genotype 2 infection: results of the real-world, clinical practice HCV-TARGET study. Issue 10 (13th July 2016) - Welzel, Tania M; Nelson, David R; Morelli, Giuseppe; Di Bisceglie, Adrian; Reddy, Rajender K; Kuo, Alexander; Lim, Joseph K; Darling, Jama; Pockros, Paul; Galati, Joseph S; Frazier, Lynn M; Alqahtani, Saleh; et al.
Abstract : Objective: Due to a high efficacy in clinical trials, sofosbuvir (SOF) and ribavirin (RBV) for 12 or 16 weeks is recommended for treatment of patients with HCV genotype (GT) 2 infection. We investigated safety and effectiveness of these regimens for GT2 in HCV-TARGET participants. Design: HCV-TARGET, an international, prospective observational study evaluates clinical practice data on novel antiviral therapies at 44 academic and 17 community medical centres in North America and Europe. Clinical data were centrally abstracted from medical records. Selection of treatment regimen and duration was the investigator's choice. The primary efficacy outcome was sustained virological response 12 weeks after therapy (SVR12). Results: Between December 2013 and April 2015, 321 patients completed 12 weeks (n=283) or 16 weeks (n=38) of treatment with SOF and RBV. Prior treatment experience and cirrhosis was more frequent among patients in the 16-week regimen compared with 12 weeks (52.6% vs 27.6% and 63.2% vs 21.9%, respectively). Overall, SVR12 was 88.2%. The SVR12 in patients without cirrhosis was 91.0% and 92.9% for 12 or 16 weeks of therapy, respectively. In patients with cirrhosis treated for 12 or 16 weeks, SVR12 was 79.0% and 83%. In the multivariate analysis, liver cirrhosis, lower serum albumin and RBV dose at baseline were significantly associated with SVR12. Common adverse events (AEs) included fatigue, anaemia, nausea, headache, insomnia, rash and flu-like symptoms. Discontinuation due to AEs occurred in 2.8%. Conclusions: In this clinical practice setting, SOF and RBV was safe and effective for treatment of patients with HCV GT2 infection. Trial registration number: NCT01474811.